Human T cells depend on functional calcineurin, tumour necrosis factor‐α and CD80/CD86 for expansion and activation in mice. (10th April 2013) - Søndergaard, H.; Kvist, P. H.; Haase, C.
Summary Dysregulated T cells are a hallmark of several autoimmune and inflammatory diseases; thus, models to study human T cells in vivo are advantageous, but limited by lacking insight into human T cell functionality in mice. Using non‐obese diabetic (NOD), severe combined immunodeficient (SCID) or recombination activating gene‐1 (RAG1)−/− and interleukin‐2 receptor gamma‐chain (IL‐2Rγ)−/− mice reconstituted with human peripheral blood mononuclear cells (PBMCs), we have studied the mechanisms of human T cell expansion and activation in mice. Injection of human PBMCs into mice caused consistent xeno‐engraftment with polyclonal expansion and activation of functional human T cells and production of human cytokines. Human T cell expansion coincided with development of a graft‐versus‐host disease (GVHD)‐like condition observed as weight loss, multi‐organ immune infiltration and liver damage. CD8+ T cells alone were sufficient for expansion and required for disease development; in contrast, CD4+ T cells alone expanded but did not induce acute disease and, rather, exerted regulatory capacity through CD25+CD4+ T cells. Using various anti‐inflammatory compounds, we demonstrated that several T cell‐activation pathways controlled T cell expansion and disease development, including calcineurin‐, tumour necrosis factor‐α and co‐stimulatory signalling via the CD80/CD86 pathway, indicating the diverse modes of action used by human T cells during expansion and activation in mice as well as the pharmacological relevance of this model. Overall, these data provide insight into the mechanisms used by human T cells during expansion and activation in mice, and we speculate that PBMC‐injected mice may be useful to study intrinsic human T cell functions in vivo and to test T cell‐targeting compounds.